Temporal Variation of N Isotopic Composition of Decomposing Legume Roots and Its Implications to N Cycling Estimates in N15 Tracer Studies in Agroforestry Systems - Riina Jalonen; Jorge Sierra (Applied and Environmental Soil Science)
Below-ground residue of agroforestry trees is an important N source for associated crops. Several studies have shown that its isotopic signature (δ15N) may change after tree pruning, which makes it difficult to study below-ground N inputs from pruned trees by isotopic techniques. We studied how temporal variation of legume root residue δ15N could be explained by considering differential decomposition kinetics and 15N content of residue fractions. A mathematical model on the isotopic patterns of soil and a N recipient plant during root decomposition was developed and applied for testing assumptions about residue characteristics against two experimental datasets. Observed 15N patterns of the recipient plants could be satisfactorily simulated only when the residue was assumed to consist of at least two fractions with distinct δ15N and decomposition rates depending on their C : N ratio. Assuming δ15N of residue constant over time resulted in substantial underestimates of N derived from low-quality residue (%Ndfr) by the recipient plant when compared with experimental data. Results of this study suggest that residue fractionation can help improve estimation of %Ndfr in isotopic studies, as an alternative or complementary method to assuming or aiming at homogenous isotopic composition of N sources.